Identification of plexin D1 on circulating extracellular vesicles as a potential biomarker of polymyositis and dermatomyositis. (23rd July 2021) - Uto, Kenichi; Ueda, Koji; Okano, Takaichi; Akashi, Kengo; Takahashi, Soshi; Nakamachi, Yuji; Imanishi, Takamitsu; Awano, Hiroyuki; Morinobu, Akio; Kawano, Seiji; Saegusa, Jun
Abstract: Objectives: We aimed to identify disease-specific surface proteins on extracellular vesicles (EVs) as novel serum biomarkers of PM/DM. Methods: We performed liquid chromatography–tandem mass spectrometry (LC/MS) on purified EVs from sera of 10 PM/DM patients, 23 patients with other autoimmune diseases and 10 healthy controls (HCs). We identified membrane proteins preferentially present in EVs of PM/DM patients by bioinformatics and biostatistical analyses. We developed an EV sandwich ELISA for directly detecting serum EVs expressing disease-specific membrane proteins and evaluated their clinical utility using sera from 54 PM/DM, 24 RA, 20 SLE, 13 SSc and 25 Duchenne and Becker types of muscular dystrophy (DMD/BMD) patients and 36 HCs. Results: LC/MS analysis identified 1220 proteins in serum EVs. Of these, plexin D1 was enriched in those from PM/DM patients relative to HCs or patients without PM/DM. Using a specific EV sandwich ELISA, we found that levels of plexin D1 + EVs in serum were significantly greater in PM/DM patients than in HCs or RA, SLE or DMD/BMD patients. Serum levels of plexin D1 + EVs were greater in those PM/DM patients with muscle pain or weakness. Serum levels of plexin D1 + EVs were significantly correlated with levels of aldolase ( r s = 0.481), white blood cells ( r s = 0.381), neutrophils ( r s = 0.450) and platelets ( r s = 0.408) in PM/DM patients. Finally, serum levels of plexin D1 + EVs decreased significantly in patients with PM/DM in clinical remission after treatment. Conclusion: We identified levels of circulating plexin D1 + EVs as a novel serum biomarker for PM/DM.